Class gaps in perceptions of political voice: liberal democracies 1974–2016. Issue 6 (19th September 2022) - Rennwald, Line; Pontusson, Jonas
Abstract: This article explores the role of occupation, education and income on individuals' perceptions of being politically represented. Based on ISSP surveys in 19 liberal democracies between 1996 and 2016 and a cross-national survey carried out in the mid-1970s, we analyse responses to the statement that 'people like me do not have any say about what the government does'. We show a clear occupational and educational hierarchy in perceptions of being politically represented (or having a political voice), with routine workers and skilled production workers perceiving themselves as much less well represented than upper middle-class professionals. Analysing changes over time, we show that class gaps were already large in the mid-1970s and increased further over the following decades. By contrast, class gaps were stable over the period from the mid-1990s to the mid-2010s. Most strikingly, we observe a sharp decline in perceived political influence among unionised workers since the 1970s. Supplemental data for this article can be accessed online at: https://doi.org/10.1080/01402382.2022.2046419 .